Refleksyvumo raiška Jokūbo Morkūno Postilės perikopėse - Maskuliūnas, Bronius (Baltistica, 2005)
THE EXPRESSION OF REFLEXIVITY IN THE PERICOPES OF JOKŪBAS MORKŪNAS’ POSTIL The article compares certain aspects of the expression of reflexivity in the pericopes of Morkūnas’ Postil with the equivalents of the Polish original – Rej’s Postil – and Baltramiejus Vilentas’ Gospels and Epistles, used by Morkūnas. The review of the pericopes of Morkūnas’ text resulted in finding 202 reflexive pronoun structures. In most cases the expression of reflexivity is non-Lithuanian when non-reflexive pronouns are used for the first and second person. About one third of these structures do not coincide with the corresponding structures used by Rej in his Postil, but almost all coincide with the text of Vilentas’ Gospels and Epistles. This confirms earlier statements that Morkūnas took the majority of the texts of pericopes from Vilentas. Altogether it should be observed, that the language of the pericopes of Rej’s Postil in terms of the expression of reflexivity is better than the language of the pericopes of the Postil by Morkūnas.